The relationship between gender discrimination andemployee well-being : An empirical study - Marwa Alaa Eldin Afifi Ghers Eldin; Kamel Ali Omran (Cairo : Marwa Alaa Eldin Afifi Ghers Eldin, 2020)
The purpose of this study is to explore the relationship between gender discrimination and employee well-being in the banking sector in Egypt. Through the study three dependent variable and one independent variablewas identified, the independent variableis: gender discrimination, also the three dependent variables are: Job-related stress, job-related depression, and job satisfaction. Also, there are three moderating variables (which are age, education and gender). The study focused on the banking sector in Egypt. A single cross-sectional study was used to conduct a descriptive conclusive study of the perception of gender discrimination and its relationship with employee wellbeing in Egyptian banks. Data were collected from the employees working in one public bank and one private. A sample of 200 respondents was gathered (n=200) using a judgmental and snowballing non-probability sampling technique. A questionnaire was used to gather data on a 7-point Likert scale. After analyzing the collected data, the research reached the following results: a) there is positive correlation between gender discrimination and job-related stress, b)there is positive correlation between gender discrimination and job-related depression, and c)there is negative correlation between gender discrimination and job satisfaction. Age, gender, and education were not found to have any moderating impact on the relationship. The research ended by developing some recommendations for banks for reducing discrimination
Thesis (M.Sc.) - Cairo University - Faculty of Commerce - Department of Business Administration
Issued also as CD
Keywords: Employee Wellbeing; Gender Discriminatio; Job Satisfaction